KEBIJAKSANAAN UPAH DAN INDUSTRIALISASI - Prijono Tjiptoherijanto (UGM, 1999)
The last two decades has seen a shift in employment in Indonesia from being agriculture based to industry and services based. Data shows that the agricultural sector still absorbs over time. Between 1987 to 1994, the percentage of the workforce employed in the agricultural sector fell from 55.91 percent to 16.15 percent, while over the same periode the figure for the industrial sector rose from 8.4 percent to 13.3 percent. This shift employment has resulted from changes occurring in the economic structure. High grwoth in the industrial sector, particularly in manufacturing and construction, has created many job opportunities in these sectors. On the contrary, the shift in the used of land from agricultural to other purposes has depressed employment opportunities in the agricultural sector. Furthermore, people perceive that working in the industrial sector provides better incentives than working in the agricultural sector. Unfortunately, the productivity of workers employed in the industrial sector is not satisfactory: employees in this sector in Indonesia are less productive than those in others ASEAN countries. Consequently, the level of wages is quite low. In order to compromise between employee and employer interests, the government sets a minimum regional wage each year. The idea behind this policy is to promote development of the industrial sector and boost employee welfare, and ever company is encouraged to determine wages according to the minimum regional wage. However, certain conditions are waived for those companies unable to comply to these minimum wage regulations.